Strong Privacy Protection in Electronic Voting - Groth, Jens; Salomonsen, Gorm (BRICS Report Series, 2004)
We give suggestions for protection against adversaries with access to the voter’s equipment in voting schemes based on homomorphic encryption. Assuming an adversary has complete knowledge of the contents and computations taking place on the client machine we protect the voter’s privacy in a way so that the adversary has no knowledge about the voter’s choice. Furthermore, an active adversary trying to change a voter’s ballot may do so, but will end up voting for a random candidate. To accomplish the goal we assume that the voter has access to a secondary communication channel through which he can receive information inaccessible to the adversary. An example of such a secondary communication channel is ordinary mail. Additionally, we assume the existence of a trusted party that will assist in the protocol. To some extent, the actions of this trusted party are verifiable.